Contribution of Autophagy-Lysosomal Pathway in the Exosomal Secretion of Alpha-Synuclein and Its Impact in the Progression of Parkinson’s Disease - Sepúlveda, Denisse; Cisternas-Olmedo, Marisol; Arcos, Javiera; Nassif, Melissa; Vidal, René L. (Frontiers in Molecular Neuroscience, 2022)
Parkinson's disease (PD) is caused by the degeneration of dopaminergic neurons due to an accumulation of intraneuronal abnormal alpha-synuclein (α-syn) protein aggregates. It has been reported that the levels of exosomal α-syn of neuronal origin in plasma correlate significantly with motor dysfunction, highlighting the exosomes containing α-syn as a potential biomarker of PD. In addition, it has been found that the selective autophagy-lysosomal pathway (ALP) contributes to the secretion of misfolded proteins involved in neurodegenerative diseases. In this review, we describe the evidence that supports the relationship between the ALP and α-syn exosomal secretion on the PD progression and its implicates in the diagnosis and progression of this pathology.